1987
DOI: 10.1017/s0317167100026147
|View full text |Cite
|
Sign up to set email alerts
|

Ecogenetics of Parkinson's Disease: Prevalence and Environmental Aspects in Rural Areas

Abstract: ABSTRACT:We make use of the unique combination of a homogeneous genetic and racial origin in the rural population of Quebec and the facilities of free and universal access to medical care, to study the distribution of the prevalence of Parkinson's disease in the 9 rural hydrographic regions of the Province. Through 3 different methods of ascertainment, confirmed by two control probes, we demonstrate that the prevalence of Parkinson's disease is of uneven distribution within rural areas. We further investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
1
4

Year Published

1990
1990
2011
2011

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(64 citation statements)
references
References 17 publications
3
54
1
4
Order By: Relevance
“…An ecological study reported high prevalence of PD in rural agricultural regions in Canada [282]. In case reports, parkinsonism was attributed to different pesticides [283][284][285][286][287][288].…”
Section: Pesticidesmentioning
confidence: 99%
See 1 more Smart Citation
“…An ecological study reported high prevalence of PD in rural agricultural regions in Canada [282]. In case reports, parkinsonism was attributed to different pesticides [283][284][285][286][287][288].…”
Section: Pesticidesmentioning
confidence: 99%
“…Beside the Canadian prevalence study [282], other prevalence studies [335][336][337] and an incidence study [338] reported higher occurrence of PD in rural than in urban areas. However, one study found lower prevalence of PD among farmers [339] and another study found slightly higher incidence in urban than in rural areas [52].…”
Section: Ecologic Studiesmentioning
confidence: 99%
“…Subsequently they postulated that the prevalence of PD might also vary in relation to environmental factors, and that the greater use of pesticides in rural areas might lead to a greater prevalence of PD (Barbeau et al, 1987). Paraquat is structurally similar to MPP+, the toxic metabolite of 1-methyl-4-phenyl-1,2,3,6,-tetrahydropyridine (MPTP) (Barbeau et al, 1985b;Snyder & D'Amato, 1985) which produces a Parkinsonian syndrome in man (Davis et al, 1979;Langston et al, 1983).…”
mentioning
confidence: 99%
“…PD risk is also associated with different -but related -environmental factors such as rural living, farming and drinking well water. Studies have shown higher occurrence of PD in rural versus urban areas in Canada (Barbeau et al, 1987), the United States (Lee et al, 2002), and Denmark (Tuchsen et al, 2000). Drinking well water is a risk factor for PD (Tsai et al, 2002); however, this tends to be dependent on rural living, so the two factors are interrelated (Koller et al, 1990).…”
Section: Parkinson's Disease (Pd)mentioning
confidence: 99%